Answer:
x=4,−2
Explanation:
Because Step 1. Move all terms to one side.
{x}^{2}-2x-8=0
x
2
−2x−8=0
2 Factor {x}^{2}-2x-8x
2
−2x−8.
1 Ask: Which two numbers add up to -2−2 and multiply to -8−8?
-4−4 and 22
Step 2. Rewrite the expression using the above.
(x-4)(x+2)
(x−4)(x+2)
and going to;
(x-4)(x+2)=0
(x−4)(x+2)=0
And Step 3. Solve for xx.
1 Ask: When will (x-4)(x+2)(x−4)(x+2) equal zero?
When x-4=0x−4=0 or x+2=0x+2=0
2 Solve each of the 2 equations above.
x=4,-2
x=4,−2
x=4,-2
Our Answer is:
x=4,−2
I Hope It's Helps